(untitled) (CIPEEX, 2023)
Founded by Baden-Powell, scouting, being non-formal education, allows its members to value the environment, preparing them for preservation and sustainable development. In this study, the practice of scouting and its socio-environmental and educational benefits for children and adolescents of the Bernardo Sayão Scout Group were analyzed through the Reduce, Recycle, and Reuse (3R’s) badge activity. Bibliographic and field research was conducted, with a qualitative approach. The theoretical framework was based on the concepts of Scouting, Environmental Education, Non-formal Education, and Transdisciplinary Education. Technical visits were conducted weekly to the Scout Group from October to November 2022. For four months, the scouts collected PET bottle caps and participated in workshops. With the guidance of a Scout Leader, they crafted with the bottle caps: tic-tac-toe, pencil holder, fidget spinner, cup and plate holder. The scouts evaluated the discarded material regarding the environment and realized the importance of responsible consumption and the reuse of bottle caps. This research demonstrated that the scouting method is a transdisciplinary education that cares about and carries out activities related to environmental and sustainability issues, such as the 3R’s Badge, promoting sustainable habits for an ecological and healthy lifestyle.